Good Governance : The IMF's Role. (Pamphlet Series; Pamphlet Series, No., 1998)
Good governance is important for countries at all stages of development... Our approach is to concentrate on those aspects of good governance that are most closely related to our surveillance over macroeconomic policies- namely, the transparency of government accounts, the effectiveness of public resource management, and the stability and transparency of the economic and regulatory environment for privalte sector activity. Michael Camdessus, IMF Managing Director.